African-centered pedagogy : developing schools of achievement for African American children - Murrell, Peter C., Jr., 1952-2015 (SUNY series, social context of education., 2002)
Based on a critical reinterpretation of several key educational frameworks, African-Centered Pedagogy is a practical guide to accomplished teaching. Murrell suggests integrating the historical, cultural, political, and developmental considerations of the African American experience into a unified system of instruction, bringing to light those practices that already exist and linking them to contemporary ideas and innovations that concern effective practice in African American communities. This is then applied through a case study analysis of a school seeking to incorporate the unified theory and embrace African-centered practice. Murrell argues that key educational frameworks-although currently ineffective with African American children-hold promise if reinterpreted.